(untitled) (Revista INTEREDU11, 2021)
This study seeks to evaluate the quality management of school coexistence in the framework of inclusion, democracy and healthy relationships. This study evaluated 267 secondary students, from two educational institutions from the city of Osorno which presented high percentage of vulnerability. This research required a quantitative, descriptive, non-experimental research design, which collected data through the application of a validated questionnaire which was applied to these students. As main results, respectful treatment from teachers to students is evident; there is support for students who presented special needs, and there is a high level of trust between students and teachers. However, although the relationships between teachers and students were well-qualified, it became clear that there were also certain differences in treatment. And in addition to that, it was not possible to evidence the existence of collaborative work between them which could allow the improvement of the quality of social relations.